FEATURES OF THE PSYCHOLOGICAL WELL-BEING OF STUDENT YOUTH - Kovalenko, Alla; Hryshchuk, Eliso; Rohal, Nina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of the article is to study the characteristics and factors of students’ psychological well-being. The basic approaches to psychological well-being studies are considered. The study was based on C. Ryff’s model, according to which psychological well-being is a complex, integral phenomenon that characterizes an individual’s positive functioning and is expressed in the subjective experience of life satisfaction, realization of one’s own potential and depends on the subjective quality of an individual’s communication with others. The empirical research tools used in the study are: Ryff's Six-factor Model of Psychological Well-being and the Questionnaire of Subjective Social Well-Being (T. V. Danylchenko). The main characteristics of modern students’ psychological profile are: independence, self-sufficiency, clearly set goals and understood ways of their implementation, a large number of trusting relationships with other people and a moderate level of control over life situations.The article shows that students’ psychological well-being is associated with their subjective social well-being: personal achievements alone do not make students feel psychologically well without their positive assessment from the side of their social environment. Based on the factor analysis results, students’ psychological well-being factors depending on their gender are identified. Boy’s psychological well-being factors are: self-sufficiency, social approval and social activity; those of girls are: self-improvement / self-realization, social noticeability (publicity), social proximity.